A multi-group analysis of car-hailing and taxi on loyalty intention in Hong Kong - Chi Ho Li; Yuk Ting Chow (International Journal of Industrial Engineering and Management, 2024)
This study proposes a Structural Equation Model (SEM) to explore the relationship between the behavior from the driver, perceived service atmosphere, perceived value, attitude and loyalty intention of customers from using taxi and car-hailing services. Meanwhile, the relationship of safety, green value, privacy, risk, sensitivity, and security as sustainability measures and customer attitude to the two services are also included in our model. Results suggest that behavior from drivers, service atmosphere, together with multiple sustainability measures, would have direct and indirect positive effects on loyalty intention, regardless of the user groups.